Time-Restricted Salutary Effects of Blood Flow Restoration on Venous Thrombosis and Vein Wall Injury in Mouse and Human Subjects - Li, Wenzhu; Kessinger, Chase W; Orii, Makoto; Lee, Hang; Wang, Lang; Weinberg, Ido; Jaff, Michael R; Reed, Guy L; Libby, Peter; Tawakol, Ahmed; Henke, Peter K; Jaffer, Farouc A (Circulation (New York, N.Y.), 2021)
Up to 50% of patients with proximal deep vein thrombosis (DVT) will develop the postthrombotic syndrome characterized by limb swelling and discomfort, hyperpigmentation, skin ulcers, and impaired quality of life. Although catheter-based interventions enabling the restoration of blood flow (RBF) have demonstrated little benefit on postthrombotic syndrome, the impact on the acuity of the thrombus and mechanisms underlying this finding remain obscure. In experimental and clinical studies, we examined whether RBF has a restricted time window for improving DVT resolution. First, experimental stasis DVT was generated in C57/BL6 mice (n=291) by inferior vena cava ligation. To promote RBF, mice underwent mechanical deligation with or without intravenous recombinant tissue plasminogen activator administered 2 days after deligation. RBF was assessed over time by ultrasonography and intravital microscopy. Resected thrombosed inferior vena cava specimens underwent thrombus and vein wall histological and gene expression assays. Next, in a clinical study, we conducted a post hoc analysis of the ATTRACT (Acute Venous Thrombosis: Thrombus Removal with Adjunctive Catheter-Directed Thrombolysis) pharmacomechanical catheter-directed thrombolysis (PCDT) trial (NCT00790335) to assess the effects of PCDT on Venous Insufficiency Epidemiological and Economic Study quality-of-life and Villalta scores for specific symptom-onset-to-randomization timeframes. Mice that developed RBF by day 4, but not later, exhibited reduced day 8 thrombus burden parameters and reduced day 8 vein wall fibrosis and inflammation, compared with controls. In mice without RBF, recombinant tissue plasminogen activator administered at day 4, but not later, reduced day 8 thrombus burden and vein wall fibrosis. It is notable that, in mice already exhibiting RBF by day 4, recombinant tissue plasminogen activator administration did not further reduce thrombus burden or vein wall fibrosis. In the ATTRACT trial, patients receiving PCDT in an intermediate symptom-onset-to-randomization timeframe of 4 to 8 days demonstrated maximal benefits in Venous Insufficiency Epidemiological and Economic Study quality-of-life and Villalta scores (between-group difference=8.41 and 1.68, respectively, <0.001 versus patients not receiving PCDT). PCDT did not improve postthrombotic syndrome scores for patients having a symptom-onset-to-randomization time of <4 days or >8 days. Taken together, these data illustrate that, within a restricted therapeutic window, RBF improves DVT resolution, and PCDT may improve clinical outcomes. Further studies are warranted to examine the value of time-restricted RBF strategies to reduce postthrombotic syndrome in patients with DVT.